Perlindungan Hukum Bagi Guru Honorer Di Lingkungan Dinas Pendidikan Kabupaten Cianjur - Nurdiansyah, Andri; Kirana Utami, Tanti; Mulyadi, Dedi (Indonesian Journal Publisher, 2026)
This study aims to analyze the forms of legal protection for honorary teachers within the Cianjur Regency Education Office and to identify various obstacles in their implementation. Honorary teachers play a strategic role in the provision of education; however, they are often in a vulnerable position due to uncertain employment status, low welfare, and limited legal protection guarantees. This research employs a normative legal research method using a statutory approach and a conceptual approach. The legal materials used consist of primary legal materials in the form of laws and regulations related to labor, education, and the state civil apparatus, as well as secondary legal materials such as literature, journals, and relevant research findings. The results of the study indicate that legal protection for honorary teachers has not been fully optimized. Normatively, there are provisions in the National Education System Law, the State Civil Apparatus Law, and various implementing regulations that provide a basis for protection; however, their implementation still faces several challenges, including limited regional budgets, the absence of proper wage standards, and unclear mechanisms for appointment as state civil servants. In addition, weak supervision and uneven regional policies further exacerbate the condition of honorary teachers. The conclusion of this study emphasizes that legal protection for honorary teachers in Cianjur Regency requires the strengthening of more specific regulations, increased commitment from local governments, and policy harmonization between central and regional governments. These efforts are essential to ensure legal certainty, justice, and welfare for honorary teachers as an integral part of the national education system.